2019
DOI: 10.1111/pcn.12848
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and negative symptoms as the characteristics of patients with schizophrenia who show competence–performance discrepancy in social functioning

Abstract: Aim Although competence and performance in relation to social functioning usually go hand in hand, it is not uncommon to observe a discrepancy between the two in patients with schizophrenia. The present study was aimed at examining the characteristics of patient groups showing such discrepancy. Methods A total of 205 outpatients with schizophrenia aged ≤40 years old were enrolled. The symptomatology and social functioning were widely assessed. The patients were divided into four groups by the cut‐off scores fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
5
11
0
Order By: Relevance
“…They adapt to their community life smoothly beyond their capacity, and clinicians often wonder at their ability to do so. In our previous study,21 we revealed and supported this fact. Namely, a certain proportion of patients with schizophrenia in the community showed a low capacity–high performance discrepancy.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…They adapt to their community life smoothly beyond their capacity, and clinicians often wonder at their ability to do so. In our previous study,21 we revealed and supported this fact. Namely, a certain proportion of patients with schizophrenia in the community showed a low capacity–high performance discrepancy.…”
Section: Introductionsupporting
confidence: 74%
“…Based on our previous findings,21 we recruited different participants who had longer duration of illness than the previous study, because decline of functional performance in patients with chronic schizophrenia is an urgent problem in clinical settings 6,39. Furthermore, the present study adopted a performance-based measure to accurately assess functional capacity,15 although we had used a self-report measure by patients in our previous study 21. Most importantly, we investigated the associations of personality traits with the capacity–performance discrepancy of functional outcome in patients with schizophrenia which have not been examined yet.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neurotic, stress-related and somatoform disorders (ICD-10 code: F4), which have a signi cant impact on social functioning [50], were the most common diagnoses ( Table 1). The proportion of F4 diagnoses in this study was higher than that for Japanese national data ( Figure 2).…”
Section: Diagnosismentioning
confidence: 99%
“…Neurotic, stress-related and somatoform disorders (ICD code: F4), which have a signi cant impact on social functioning [48], were the most common diagnoses ( Table 1). The proportion of F4 diagnoses in this study was higher than that for Japanese national data ( Figure 2).…”
Section: Diagnosismentioning
confidence: 99%